Comparison Of Tilawah Memorization And Conventional Methods In Early Childhood At Ra Plus Ja-Alhaq, Bengkulu City - Indri Septiani; Ahmad Suradi; Budrianto (Yayasan Azhar Amanaa Yogyakarta, 2025)
This study aims to compare the effectiveness of the Tilawah method and the conventional method in improving the ability of early childhood students to memorize short Qur'anic surahs. This research employed a quantitative approach with a quasi-experimental design using a non-equivalent control group design. The participants consisted of 42 children aged 5–6 years at RA Plus Ja-Alhaq Bengkulu City, divided into an experimental group and a control group. Data were collected through observation, memorization tests, and documentation. Data analysis involved validity testing, reliability testing, normality testing, homogeneity testing, and independent sample t-test. The findings revealed a significant difference between the memorization abilities of children taught using the Tilawah method and those taught using the conventional method. The Tilawah method was more effective in enhancing children's memorization skills due to its emphasis on repetition, listening activities, and rhythmic recitation. Therefore, the Tilawah method is recommended as an alternative learning strategy for improving Qur'anic memorization among early childhood learners.